PERGESERAN OTORITAS SOSIAL DAN KULTURAL GURU: ANALISIS SOSIO-ANTROPOLOGIS KONFLIK PENDIDIK DAN ORANG TUA DALAM KASUS PENDISIPLINAN SISWA DI JAMBI - Hamzah Irfanda; Yana Alfita Dea Nova; Suci Herdayanti; Juriya Adhandini; Fajri Afrialdi (Yayasan Literasi Sains Indonesia, 2026)
This study examines shifts in teachers' social and cultural authority through a socio-anthropological analysis of conflicts between educators and parents regarding student discipline in Jambi. The study is motivated by the increasing criminalization of teachers stemming from disciplinary actions at school that escalate into legal and social issues, a trend exacerbated by digital media's role in accelerating public judgment. A qualitative approach was employed, utilizing case study methods within a constructivist paradigm. Primary data were obtained through content analysis of the viral video